EVALUATION OF COGNITIVE PERFORMANCE IN OLDER ADULT RESIDENTS OF A RURAL AREA - Juliana Bessa Martins; Celmira Lange; Marcos Aurélio Matos Lemões; Patrícia Mirapalheta Pereira de Llano; Fernanda dos Santos; Janaína Amorim de Avila (Universidade Federal do Paraná, 2016)
The aim of this study was to describe the cognitive performance of older adults living in a rural area.This was a descriptive, quantitative, cross-sectional study, with older adults, aged 60 or more, living in the rural area of a municipality in the south of Brazil, which took place between July and October 2014. The study sample was 806 older adults.The majority of the older adults participants were aged 60-69 years, with 4-7 years of schooling and 450 (55.83%) were female.The mean in the Mini-Mental State Examination was 23.59, standard deviation 5.21. The men presented a higher mean in this scale than the women (p<0.001). Differences in the mean for age were not significant (p=0.8). These results may serve to support health professionals and managers in the creation of cognitive decline prevention strategies.